Oak Tree, Gum Tree: Screen Collaborations Across Time Zones - Gough-Brady, Catherine; Rogers, Christine (Journal of Anthropological Films, 2023)
Oak Tree, Gum Tree, a collaborative video work by award-winning filmmakers Catherine Gough-Brady and Christine Rogers, explores the way that audio-visual material can “embrace the complexity of the world” and “incorporate, within their structures and production processes, multiple voices that “utter” together in the creation of content” (Aston and Odorico, 2018, p. 63). Aston and Odorico use this polyphonic approach as a way of exploring relationships between documentary works and audience. Gough-Brady and Rogers are interested in seeing how this approach can be applied between filmmakers and images themselves. Can images be ascribed what Bennett calls ‘vibrancy’ (2010) and have agency in how they are cut together? How much of this becomes an expression of the filmmaker through the images? This work was selected for exhibition at the International Visual Sociology Association conference in 2022. Works cited Aston, J and Odorico, S. (2018). The Poetics and Politics of Polyphony: Towards a Research Method for Interactive Documentary, Aphaville issue 15, Summer